Getting down to work: the employment attitudes of persons with a felony conviction and their behavioral implications - Lucken, Karol (Journal of crime and justice, 2023)
The employment of persons with a felony conviction has been historically problematic. This has been partly attributed to deficits in educational/vocational training and interpersonal skills as well as certain occupational prohibitions and biases against hiring those with a criminal record. Programmatic and policy efforts to reduce these deficits and barriers have been fairly numerous, but they have also fallen short of expectation. The desired outcomes for these efforts, namely job attainment and ideally lower recidivism, have been typically modest or uncertain. In weighing this shortfall, scholars have proposed that a better understanding of employment outcomes for persons with a criminal record requires a better understanding of their attitudes about employment. Based on growing research in this area, the current study examines various attitudes on employment and the connection between those attitudes and two key contingencies, namely current job status and beliefs about the inhibiting effect of employment on future criminal behavior. In discerning these attitudes and their behavioral implications, the relative impacts of several criminological and psychological variables are explored. The findings are generated from the survey responses of 179 males with felony convictions who were on community supervision in a large urban county in Florida.